Improving the Efficiency of the Low-Voltage Potential Application Method at Top Oxygen Blowing in Converter - Semykin, S.I.; Golub, T.S.; Dudchenko, S.O. (Science and Innovation, 2024)
Introduction. The main factor of oxygen blowing in converters is the interaction of oxygen jet with the molten metal bath. It determines hydrodynamics, heat and mass transfer, slag formation and causes metal losses with emissions affecting the yield of liquid steel. Problem Statement. The most promising research aimed at improving the slag formation and increasing the yield of liquid steel in the conditions of modern metallurgical practice. It deals with the electro physical effects on the metal smelting process. It includes the method of low-voltage potentials application developed in the Iron and Steel Institute of Z.I. Nekrasov of the NAS of Ukraine (ISI NASU). Purpose. To study the possibilities and to evaluate ways to improve the efficiency of the method of low-voltage potential application for top oxygen blowing in the converter. Materials and Methods. The tests were carried out on a 160-ton industrial oxygen converter equipped with a device for low-voltage potential application on the lance and a metal bath with imposition of a negative or positive polarity to the lance throughout the blowing period. The top blowing option through five nozzle tip has been studied while producing medium carbon steel with intermediate deslagging. Results. The analysis of the array of experimental industrial heats carried out in 160-t converters in conditions of low-voltage potential application, has made it possible to identify the following patterns of changes in the electrical characteristics of the bath from the blowing parameters. It was established that regardless of the polarity of the potential at the lance, the magnitude of the values of current and useful power of impact in lance–metal bath circuit over blowing periods depends on: the level of the voltage at the source of current and the height of the lance in the converter's volume above the metal bath. Thus, it is necessary to maintain the position of the lance: from the beginning of the blowing, depending on the location of the scrap, at a height of 0.9-1.0 m, in the main blowing period, at 1.0-1.2 m, and in the final period, at 1.0-1.1 m, which is made taking into account the effective support of the current during the blowing at an adequate level to achieve the maximum level of the effect of the low voltage potential application. Conclusions. Industrial testing of the recommended blow mode in 160-t converters showed the possibility to almost double the efficiency of using low-voltage potential application compared with the previously developed and accepted at the plant mode of its application.